2015
DOI: 10.1515/bpasts-2015-0053
|View full text |Cite
|
Sign up to set email alerts
|

Influence of convective heat and mass conditions in MHD flow of nanofluid

Abstract: Abstract. This article aims to investigate the two-dimensional magnetohydrodynamic (MHD) boundary layer flow of nanofluid. Convective mass condition is introduced. Analysis has been discussed in the presence of an applied magnetic field. The Brownian motion and thermophoresis effects are incorporated. The arising nonlinear problems are first converted to ordinary differential equations and then series solutions are constructed. Convergence of series solutions is examined through plots and numerical values. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 38 publications
3
20
0
Order By: Relevance
“…Fig. 9 Tables 4 and 5 give the comparison of present results in a limiting sense with the work done by Shehzad et al [37]. It is found that the obtained results in limiting sense are in good agreement with that of Shehzad et al [37].…”
Section: Accepted Manuscriptsupporting
confidence: 84%
“…Fig. 9 Tables 4 and 5 give the comparison of present results in a limiting sense with the work done by Shehzad et al [37]. It is found that the obtained results in limiting sense are in good agreement with that of Shehzad et al [37].…”
Section: Accepted Manuscriptsupporting
confidence: 84%
“…The theoretical investigation of MHD Williamson nanofluid in a tapered asymmetric channel under the action of a thermal radiation parameter with peristalsis was studied by Kothandapani and Prakash (2015) and the authors have indicated that such analysis may serve for the intrauterine fluid motion in a sagittal cross-section of the uterus under cancer therapy and drug analysis. More recently, Shehzad et al (2015) have investigated the two-dimensional magnetohydrodynamic (MHD) boundary layer flow of nanofluid in the presence of an applied magnetic field with Brownian motion and thermophoresis effects. Mixed convection flow through a channel has be en extensively studied 2 because of its occurrence in many practical applications such as the cooling of modern electronic systems, heat exchangers, solar energy collection, chemical processing equipments, transport of heated or cooled fluids, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The transformed boundary layer approximations for velocity, energy and concentrations are contemplated by the homotopy analytic method (HAM). Some prominent literature on the HAM are [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] and the references therein. The dimensionless velocity, temperature and nanoparticles concentration are discussed in the form of graphs in view of several governing parameters.…”
Section: Introductionmentioning
confidence: 99%